RESILIENSI PADA REMAJA YATIM PIATU YANG TINGGAL DI PANTI ASUHAN - Grace Kusuma Dewi; Berliana Henu Cahyani (JURNAL SPIRITS, 2015)
Abstract The aim of this reseach is to know how far the resilence of juvenile orphan in facing social relation and life problem. Subject of this reseach is juvinile orphan who live in orthanage and concist of two people.Reseach method that is used in this reseach is interview and observation. Analitical technic used in this reseach is data colecting, data reduction, data presentation, data trianggulation, and to conclude the existing data. Data analys result is there are four aspects that is found 25 variabel catagory resilience of juvinile orphan, includes of factors that influence the resilience, characteristic resilience, spesific resilience, domain, spesification of the individual resilience. There are 3 catagories and 16 sub catagories factors that influence the resilience. The second aspect is characteristic resilience, there are 7 catagories and 11 sub catagories. The third aspect is spesification resilience domain, there are 3 catagories and 8 sub catagories. The fourh aspect is spesification of the individual resilience , there are 12catagories and 23 sub catagories. Key Word : The Juvenile, Resilience